Do Inpatient Antimicrobial Stewardship Programs Help Us in the Battle Against Antimicrobial Resistance?. (15th July 2020) - Tartof, Sara Y; Chen, Lie Hong; Tian, Yun; Wei, Rong; Im, Theresa; Yu, Kalvin; Rieg, Gunter; Bider-Canfield, Zoe; Wong, Frances; Takhar, Harpreet S; Qian, Lei
Abstract: Background: Antibiotic stewardship programs (ASPs) have demonstrated success at reducing costs, yet there is limited quality evidence of their effectiveness in reducing infections of high-profile drug-resistant organisms. Methods: This retrospective, cohort study included all Kaiser Permanente Southern California (KPSC) members aged ≥18 years hospitalized in 9 KPSC hospitals from 1 January 2008 to 31 December 2016. We measured the impact of staggered ASP implementation on consumption of 18 ASP-targeted antibiotics using generalized linear mixed-effects models. We used multivariable generalized linear mixed-effects models to estimate the adjusted effect of an ASP on rates of infection with drug-resistant organisms. Analyses were adjusted for confounding by time, cluster effects, and patient- and hospital-level characteristics. Results: We included 765 111 hospitalizations (288 257 pre-ASP, 476 854 post-ASP). By defined daily dose, we found a 6.1% (−7.5% to −4.7%) overall decrease antibiotic use post-ASP; by days of therapy, we detected a 4.3% (−5.4% to −3.1%) decrease in overall use of antibiotics. The number of prescriptions increased post-ASP (1.04 [1.03–1.05]). In adjusted analyses, we detected an overall increase in vancomycin-resistant enterococci infections post-ASP (1.37 [1.10–1.69]). We did not detect a change in the rates of extended-spectrum beta-lactamase, carbapenem-resistant Enterobacteriaceae, and multidrug-resistant Pseudomonas aeruginosa infections post-ASP. Conclusions: ASPs with successful reductions in consumption of targeted antibiotics may not see changes in infection rates with antibiotic-resistant organisms in the 2 to 6 years post-implementation. There are likely differing timescales for reversion to susceptibility across organisms and antibiotics, and unintended consequences from compensatory prescribing may occur. Abstract : This comprehensive study across 9 hospitals with staggered implementation of antibiotic stewardship programs (ASPs) detected reduced consumption of most targeted antibiotics, yet unchanged infection rates of extended-spectrum beta-lactamase, carbapenem-resistant Enterobacteriaceae, and multidrug-resistant Pseudomonas aeruginosa. We detected increased rates of vancomycin-resistant enterococci infections post-ASP.